ENHANCING STUDENT LEARNING OUTCOMES THROUGH YOUTUBE AUDIO-VISUAL MEDIA IN JUNIOR HIGH SCHOOL - Muhammad Hafizh Ifandi (MEDIA DAN STRATEGI PEMBELAJARAN, 2024)
This study aims to determine: (1) student learning outcomes before the use of visual media in fiqh subjects. (2). The use of visual media in improving the learning outcomes of fiqh subjects. (3) student learning outcomes after using visual media in fiqh subjects. The type of research used is Classroom Action Research (CAR) with a qualitative approach. This research is more like solving a problem whose results are described as a whole. The research subjects in this PTK were grade 2 students of MTs Al-Kasyif Kebon Orong. The results of this study indicate that; 1) In this research the application of audio-visual media is applied because there is still a lack of students' scores in Fiqh subjects, especially in Hajj and Umrah materials. So the application of audio-visual media is applied to improve student learning outcomes in fiqh subjects (2) in cycle I, 15 students achieve completeness, and 10 students do not complete with an average score of 76.4%. whereas (3) in cycle II 23 students achieved completeness and 2 students did not complete with an average score of 86.7%, the use of visual media can improve student learning outcomes in fiqh subjects, it can be concluded that what is what the researcher wanted at the beginning of the research has been achieved so that this research can be said to be successful and not to be continued in the next